2005
DOI: 10.1161/01.atv.0000161274.87407.26
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Uric Acid, Metabolic Syndrome, and Carotid Atherosclerosis in Japanese Individuals

Abstract: Objective-There are few data available on possible independent association between uric acid and carotid atherosclerosis.Here we first sought to investigate association between uric acid levels and metabolic syndrome in Japanese; second, we assessed whether there is an independent association of uric acid with prevalence of carotid atherosclerosis in individuals subdivided according to gender and metabolic syndrome status. Methods and Results-Cross-sectional data from 8144 individuals who underwent general hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
197
6
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(228 citation statements)
references
References 46 publications
18
197
6
4
Order By: Relevance
“…Subclinical, low-grade inflammation and hyperuricaemia are frequently associated with several components of MS as well as with functional and structural alterations of the arterial bed. [25][26][27][28][29][30] Nevertheless, in this study, the relationship between arterial stiffness and MS was independent of hs-CRP and uric acid. As for gender influence, patients with MS were more frequently male; however, AASI levels were higher in these patients regardless of gender.…”
Section: Discussioncontrasting
confidence: 68%
“…Subclinical, low-grade inflammation and hyperuricaemia are frequently associated with several components of MS as well as with functional and structural alterations of the arterial bed. [25][26][27][28][29][30] Nevertheless, in this study, the relationship between arterial stiffness and MS was independent of hs-CRP and uric acid. As for gender influence, patients with MS were more frequently male; however, AASI levels were higher in these patients regardless of gender.…”
Section: Discussioncontrasting
confidence: 68%
“…They again found that the total bilirubin level was negatively associated with carotid plaque in men and women (9). Furthermore, the total bilirubin level was inversely correlated with metabolic syndrome (9). Recently, Erdogan et al (10) (2,13).…”
Section: Discussionmentioning
confidence: 94%
“…The same group of investigators later conducted a larger correlation study on 8,144 subjects who underwent a general health check-up (9). They again found that the total bilirubin level was negatively associated with carotid plaque in men and women (9).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, the ORs for metabolic syndrome increase with the gender-specific quartiles of uric acid levels after adjusting for age, total cholesterol and smoking status in Japanese adults. 29 In a population-based study, Onat et al 30 have shown that the OR of metabolic syndrome is 1.89 using the top-versus-bottom tertile of uric acid level adjusting for possible confounders. In addition, uric acid is independently correlated with number of metabolic syndrome components.…”
Section: Discussionmentioning
confidence: 99%